Epidemiology of Acute Kidney Injury After Neonatal Cardiac Surgery: A Report From the Multicenter Neonatal and Pediatric Heart and Renal Outcomes Network. Issue 10 (24th June 2021) - Alten, Jeffrey A.; Cooper, David S.; Blinder, Joshua J.; Selewski, David T.; Tabbutt, Sarah; Sasaki, Jun; Gaies, Michael G.; Bertrandt, Rebecca A.; Smith, Andrew H.; Reichle, Garrett; Gist, Katja M.; Banerjee, Mousumi; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Cardiac surgery–associated acute kidney injury occurs commonly following congenital heart surgery and is associated with adverse outcomes. This study represents the first multicenter study of neonatal cardiac surgery–associated acute kidney injury. We aimed to describe the epidemiology, including perioperative predictors and associated outcomes of this important complication. DESIGN: This Neonatal and Pediatric Heart and Renal Outcomes Network study is a multicenter, retrospective cohort study of consecutive neonates less than 30 days. Neonatal modification of The Kidney Disease Improving Global Outcomes criteria was used. Associations between cardiac surgery–associated acute kidney injury stage and outcomes (mortality, length of stay, and duration of mechanical ventilation) were assessed through multivariable regression. SETTING: Twenty-two hospitals participating in Pediatric Cardiac Critical Care Consortium. PATIENTS: Twenty-two–thousand forty neonates who underwent major cardiac surgery from September 2015 to January 2018. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Cardiac surgery–associated acute kidney injury occurred in 1, 207 patients (53.8%); 983 of 1, 657 in cardiopulmonary bypass patients (59.3%) and 224 of 583 in noncardiopulmonary bypass patients (38.4%). Seven-hundred two (31.3%) had maximum stage 1, 302 (13.5%) stage 2, 203 (9.1%) stage 3; prevalence of cardiac surgery–associated acute kidney injury peaked on postoperative day 1. Cardiac surgery–associated acute kidney injury rates varied greatly (27–86%) across institutions. Preoperative enteral feeding (odds ratio = 0.68; 0.52–0.9) and open sternum (odds ratio = 0.76; 0.61–0.96) were associated with less cardiac surgery–associated acute kidney injury; cardiopulmonary bypass was associated with increased cardiac surgery–associated acute kidney injury (odds ratio = 1.53; 1.01–2.32). Duration of cardiopulmonary bypass was not associated with cardiac surgery–associated acute kidney injury in the cardiopulmonary bypass cohort. Stage 3 cardiac surgery–associated acute kidney injury was independently associated with hospital mortality (odds ratio = 2.44; 1.3–4.61). No cardiac surgery–associated acute kidney injury stage was associated with duration of mechanical ventilation or length of stay. CONCLUSIONS: Cardiac surgery–associated acute kidney injury occurs frequently after neonatal cardiac surgery in both cardiopulmonary bypass and noncardiopulmonary bypass patients. Rates vary significantly across hospitals. Only stage 3 cardiac surgery–associated acute kidney injury is associated with mortality. Cardiac surgery–associated acute kidney injury was not associated with any other outcomes. Kidney Disease Improving Global Outcomes criteria may not precisely define a clinically meaningful renal injury phenotype in this population.